Floods and flood management and its socio-economic impact on Pakistan: A review of the empirical literature - Manzoor, Zaira; Ehsan, Muhsan; Khan, Muhammad Bashir; Manzoor, Aqsa; Akhter, Malik Muhammad; Sohail, Muhammad Tayyab; Hussain, Asrar; Shafi, Ahsan; Abu-Alam, Tamer; Abioui, Mohamed (Frontiers in Environmental Science, 2022)
Flood is the most damaging natural disaster and the recent floods have shown their serious impact on Pakistan. Flood control and regulation policies are essential to reduce the risks of economic downturn, a threat to human existence, and to sustain the ecological environment. The severity of flood catastrophe activities represents a constant and severe issue in the world. Floods are rising year by year in severity and duration, causing negative impacts on the social and economic conditions of the nation concerned. While the frequency of floods cannot be avoided, their adverse impacts can be considerably reduced by adopting careful planning and efficient training. This paper analyses the existing condition of flood control policies outlines the flood protection problems, and the socio-economic impact of severe floods, and discusses opportunities for successful and efficient flood control in Pakistan. The paper also intends to propose several suggestions for efficient and sustainable flood control in Pakistan.